A study of the magneto-controlled mechanical properties and polishing performance for single-crystal SiC used as a magnetorheological-elastomer polishing pad. (7th February 2022) - Hu, Da; Deng, Jiayun; Lu, Jiabin; Yan, Qiusheng; Du, Canlin; Cao, Jiyang
Abstract: Magnetorheological elastomers (MREs) are widely used in vibration control due to their excellent magneto-controlled mechanical properties. In this research, polyurethane-based MRE polishing pads were prepared and used for the polishing of single-crystal SiC to investigate the magneto-controlled mechanical properties, the magneto-polishing effect, and the mechanism of action thereof. The results show that the pre-structuring process is affected by parameters such as mass fraction and particle size of magnetic particles in MREs and curing magnetic field strength, different chain strings that demonstrate different magnetorheological effects are formed. The greater the mass fraction of magnetic particles and curing magnetic field strength, the more the MREs exhibit magnetorheological effects, especially so when the magnetic particles size of 3 μ m. A series of 90 min polishing experiments on single-crystal SiC with original surface roughness ( R a ) 80 nm were conducted using an MRE pad. The results indicate that with the increase of polishing magnetic field strengths, the shear modulus of MRE polishing pads increases, the material removal rate (MRR) of the polishing process increases and R a decreases. As the magnetic field strength is increased from 0 mT to 335 mT, the shear modulus is increased from 1.392 MPa to 1.825 MPa (an increase of 31.1%), while MRR is increased from 706.3 nm h −1 to 835.3 nm h −1 (an increase of 18.3%), R a is decreased from 19.92 nm to 3.62 nm (an improvement in surface quality of 81.8%). The results show that the increase of the polishing magnetic field strengths changes the material modulus of the MRE polishing pads, which cause the decreases in the compressive and shear elastic deformation of the abrasive grains on the elastic substrate. This increases the positive pressure of the abrasive grains on the SiC wafer, which enhances the material-removal ability of the SiC wafer, thereby improving the surface quality of the wafer.